Study on the first phase of the 100-day employment generation programme - NFPCSP; BRAC (RED); BDI of BRAC University (BRAC, 2019)
In September 2008, the Government of Bangladesh embarked on the first phase of a 100-day Employment Generation Programme (EGP) for the poorest and jobless poor. This endeavour came in response to the soaring food price. NFPCSP was requested by the Government to assist in the appraisal of the programme through an evaluation of its first phase and the preparation for the assessment of the impact of the entire programme.